Interosseous Membrane of the Forearm - Matthias, Robert; Wright, Thomas W. (Journal of Wrist Surgery, 2016)
Background Injuries of the interosseous membrane (IOM) of the forearm are frequently unrecognized, difficult to treat, and can result in a devastating sequelae for the wrist and elbow.Purpose The purpose of this review article is to evaluate the dignosis, biomechanics, clinical results, and propose a treatment approach to this rare complex entity.Methods The biomechanical and clinical literature is reviewed. A treatment approach is described based on the known biomechanics and clinical experience of the senior author (T. W. W.).Results Multiple different reconstructive methods have been proposed for the treatment of both acute and chronic IOM injuries. The results of the published series are reviewed. IOM injuries can have reasonable outcomes particularly if diagnosed and treated early.Conclusion There are multiple methods for treating patients with IOM injuries. Physicians should be highly suspicious about this injury when a patient presents with a highly displaced radial head fracture associated with wrist pain. Treatment with reconstruction of the cerebral band of the IOM with radial head replacement (do not overstuff) and temporary uploading the construct with K-wires from the ulna to the radius will give the most predictable results.
Keywords: central band; distal radial ulnar joint; Essex–Lopresti injury; interosseous membrane; proximal radial ulnar joint